2-Nitroterephthalato-based uranyl coordination polymers: Selective luminescent sensing for vitamin B5 and Cr2O72–. (February 2023) - Lv, Pei; Liu, Nan; Mao, Sheng-Bin; Li, Wen-Ying; Fu, Yu; Xu, Wei
Abstract: Under solvothermal conditions, a series of new uranyl coordination polymers based on 2-nitroterephthalic acid (H2 ntp) and additional auxiliary ligands were successfully synthesized, which can be denoted as (UO2 )(ntp)(dm-phen) (1 ), (Hphen)2 ∙[(UO2 )(ntp)1.5 ]2 (2 ), (Hphen)2 ∙[(UO2 )2 (ntp)3 ]∙(H2 O)2 (3 ), and (Hphen)2 ∙[(UO2 )2 (ntp)2.5 ]2 ∙(H2 O)2 (4 ) (dm-phen = 4, 7-dimethyl-1, 10-phenanthroline, phen = 4, 7-phenanthroline). The characteristics of as-prepared compounds were revealed by single crystal and powder X-ray diffraction, thermogravimetry, infrared spectroscopy and luminescent measurement. Furthermore, Compound 2 presents excellent sensitivity and selectivity to sense vitamin B5 (VB5 ) and Cr2 O7 2− anion as a dual-functional luminescent sensor in aqueous solution. 2 is the first turn-on luminescent sensor for detecting VB5 with a low detection limit (LOD) of 1.39 μM, and the experimental detection range was 10–90 μM. In addition, in the linear range of 50–450 μM, 2 also exhibits obvious luminescence quenching effect for Cr2 O7 2− anion with the LOD value of 7.27 μM. This work possesses potential application in detecting VB5 in newborn calf serum and Cr2 O7 2− in river water samples. Graphical abstract: Image 1 Highlights: Four novel uranyl coordination polymers have been synthesized under solvothermal conditions. Compound 2 is the first luminescent probe to detect VB5 with "turn-on" sensing method. Compound 2 also have "turn-off" fluorescence sensing property of Cr2 O7 2− . The mechanisms of 2 sensing VB5 and Cr2 O7 2– are discussed in detail.